Pyrolysis of Puspa Wood Sawdust and Sugarcane Bagasse into Biochar - Wan Ryan Asri; Hasanudin Hasanudin; Ady Mara; Desnelli Desnelli (Aceh International Journal of Science and Technology, 2022)
Puspa wood sawdust and sugarcane bagasse are abundantly available but have low carbon content and nutrients. The carbon content and nutrients could be increased by converting biomass into biochar through pyrolysis. The independent variables of pyrolysis were essential to investigate because those inherently influence biochar quality. In this study, the effect of pyrolysis temperature (300, 350, 400, 450, and 500 ˚C) and time (30, 60, 90 mins) on the biochar characteristic such as pH, yield, and proximate compositions were determined. The total nitrogen, P2O5, and K2O content at optimum condition biochar were also investigated. The data analysis showed that the pyrolysis temperature and time increment positively correlated to the pH, ash content, and carbon content. At the same time, the yield and volatile matter were vice versa. Both biochar's optimum pyrolysis temperature and time were achieved at 500 and 90 minutes. The carbon content and nutrient of biochar were also increased compared to the biomass. The pyrolysis method has enhanced biomass quality, and the biochar may be used as a growing media and soil amendment. It can be concluded that the sugarcane bagasse biochar was more likely favorable than puspa wood sawdust biochar due to its higher fixed carbon and nutrient content